Transliteration recognition of Tibetan person name based on Tibetan cultural knowledge. (8th May 2020) - Wang, Zhijuan; Fang, Wenguang; Zhao, Xiaobing; Song, Wei; Feng, Yinghui; Chang, Yining
Institute of Computing Technology, Chinese Lexical Analysis System (ICTCLAS) is a common tool for Chinese word segmentation and named entity recognition. With this tool, the F1 value of person name recognition from Chinese texts in Tibetan culture is only 40%. We propose a method for transliteration recognition of Tibetan person name based on Tibetan cultural knowledge. Firstly, we leverage Tibetan cultural dictionary to improve the word segmentation performance of ICTCLAS. Then, special contextual features and naming rules of Tibetan person name in their culture are adopted to determine the boundary of Chinese transliteration of Tibetan person name. Finally, the transliteration candidates of Tibetan person name are filtered based on discrimination and reliability. Experiments on a 1.2 M Tibetan text in Tibetan culture show that the method can increase the F1 value of Chinese transliteration recognition of Tibetan person name from 40.08% to 87.92% in ICTCLAS.